2004
DOI: 10.1590/s1517-83822004000300008
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic action of Lentinula edodes and Agaricus blazei on Aspergillus nidulans conidia

Abstract: The antimutagenic effect of the mushrooms Lentinula edodes and Agaricus blazei was studied on conidia of Aspergillus nidulans when exposed to short wave ultraviolet light. Two strains of A. nidulans were used. For the preparation of the extracts, the fresh mushrooms were left in aqueous infusion for 12 hours and heated in a water bath for 15 min at 100ºC, and then the material was filtered. The dehydrated mushrooms were left in aqueous infusion for 12 hours and to filtrated. Both filtrates were used as extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
(11 reference statements)
1
8
0
1
Order By: Relevance
“…These results are in accordance with other authors who also report no toxicity of A. subrufescens basidiocarp extracts [10,14,[19][20][21][22]26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in accordance with other authors who also report no toxicity of A. subrufescens basidiocarp extracts [10,14,[19][20][21][22]26].…”
Section: Discussionsupporting
confidence: 93%
“…blazei Murrill sensu Heinemann [12]; =A. brasiliensis Wasser et al [28]) has antimutagenic [23], antitumor [5,19], immune stimulating [10], antioxidant [20], anti-inflammatory [21], and UV protecting [26] activities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the 4% concentration reduced the frequency of spontaneous mutations compared to the Control, which suggests the mucilage of the leaves may possess antioxidant effects. This system-test is efficient and has been used in other investigations of phytotherapeutic products such as the study by Rodrigues et al (2003) on the mushroom of the Sun (Agaricus blazei) and Souza-Paccola et al (2004) who investigated the Lentinula edodes and A. blazei mushrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Agaricus brasiliensis Wasser et al (A. blazei Murrill sensu Heinemann), , also denoted A. subrufescens (KERRIGAN, 2005), is a fungus native to Brazil (BRAGA et al, 1998;COLAUTO et al, 2002;DIAS et al, 2004;EIRA, 2003; and it has been reported many therapeutic properties (KIM et al, 2005;KIMURA et al, 2004;MIZUNO, 2002;OSHIMAN et al, 2002;RODRIGUES et al, 2003;SOUZA-PACCOLA et al, 2004). It has been produced in Brazil for commercial purposes since 1990 and 90% of its current production is exported to Japan (EIRA, 2003).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%